Metodologia para identificação de fatores estratégicos para acompanhamento sistemático da evasão em cursos de graduação - Hoffmann, Ivan Londero (2016)
The dropout in undergraduation education is a complex phenomenon and it is a concern in the management of academic institutions. The most reliable data regarding dropout in Brazil are published annually by the Ministry of Education, which annually conducts the Census of Undergraduation Education. However, inside the institutions, knowledge that can be used to control dropout rates is dispersed in the individual knowledge of people, making it difficult to planning effective actions to combat dropout. Managers often have an empirical knowledge of the subject and develop normally intuitive actions. This paper presents a methodology that allows the identification of strategic factors capable of supporting a systematic monitoring of dropout rates. With an exploratory and quantitative approach, the work was divided into two stages. The first stage was carried out a systematization of data from the case study of the environment, for the analysis of dropout, using Census as a data source. The result was the demonstration that, from the Census data, the indicators can be extracted systematically and involve all courses and institution centers. In the second stage of the research, we sought to tacit knowledge of the institution's experts made up of teachers who passed the courses coordinating role. This step used the Delphi method of scientific research, to define consensually, which factors are most important and which justify the high dropout rates in the institution. As a result, we have elaborated a panel on which are listed the main causes of dropout. From this panel, which represents the socialization of knowledge, the managers can develop institutional policies, strategies and actions that minimize these factors and their influence on dropout rates of the institution.